An exact solution for the problem of flexure of a composite beam with preliminarily strained layers under large strains. Part 2. Solution for different types of incompressible materials. (1st December 2016) - Levin, Vladimir A.; Zubov, Leonid M.; Zingerman, Konstantin M.
Abstract: The exact solution of the problem of flexure of nonlinear-elastic composite beam with preliminarily strained layers is analyzed for large strains. The solution is obtained using the theory of superposition of large strains. Numerical results are shown for the Bartenev–Khazanovich material and for Biderman material. Nontrivial effects caused by nonlinearities are discussed.